STUDY ON AN IMMUNOGLOBULIN PREPARATION'S PENETRATION INTO BILE - YURA, JIRO; MIZUNO, AKIRA; MASHITA, KEIJI; SHINAGAWA, NAGAO (CHEMOTHERAPY, 1989)
Five grams of a pepsin-treated human immunoglobulin preparation was administered by i. v. drip infusion over 60 min to 4 patients undergoing T-tube drainage of the common bile duct, and the preparation's passage into bile was studied. Its binding to clinical isolates of Pseudomonas aeruginosa and Escherichia coli was also examined in vitro. The results were as follows:(1) The biliary and serum levels of the preparation both reached the maximum 4 h after administration, with peak levels ranging from 3.6 to 23μg/ml and from 406 to 2, 586μg/ml, respectively.(2) Fluorescent microscopy showed that the preparation was able to bind to the bacteria in vitro at concentrations of down to 0.01μg/ml. The above results suggest the usefulness of the immunoglobulin preparation in biliary tract infection.